The effects of ruminally protected lysine supplementation to growing steers and guanidinoacetic acid supplementation to milk-fed calves - Hazlewood, Kathryn Jean (Kansas State University, 2022)
Studies were conducted to assess growth performance of 1) limit-fed growing cattle when supplemented ruminally protected lysine and 2) milk-fed calves when supplemented guanidinoacetic acid. The first study utilized 340 crossbred steers (250 ± 3.8 kg) in a 77-day growing trial to access the effects of ruminally protected lysine supplementation when limit-fed a corn-based diet. Steers were allocated to 4 blocks with 8 pens, each containing 9 to 12 steers, that were assigned treatments in a randomized block design. Treatments included a control, 3 g /day metabolizable Lys provided by Smartamine ML (Lys-3; Adisseo, Alpharetta, GA), 6 g metabolizable Lys/day from Smartamine ML (Lys-6), and blood meal (BM; AAdvantage; Perdue Agribusiness, Kings Mountain, NC) provided at 0.89% of dietary dry matter to increase metabolizable Lys by 3 g/day plus 2 g/day of metabolizable Met from Smartamine M. Diets included 10% dry-rolled corn, 29.5% steam-flaked corn, 40% wet corn gluten feed, 13% hay, and 7.5% supplement. Steers were limit-fed at 2.4% of body weight once daily. Steers were implanted (40 mg trenbolone acetate, 8 mg estradiol) at trial initiation. Tail vein blood samples were collected on day 14 and 77 for analysis of plasma amino acid concentrations, urea, and haptoglobin. Performance during the growing phase was measured by weekly pen weights. After completion of the 77 days, steers were shipped to a commercial feedlot, mixed into 2 finishing pens, and fed a common diet without treatment for 185 or 206 days then harvested commercially. Performance during the finishing phase was calculated using carcass data acquired from the abattoir. During the growing phase, Lys-3 tended to improve average daily gain by 0.11 kg/day (quadratic, P = 0.12) and efficiency of gain (quadratic, P = 0.08) compared to control. Plasma concentrations of most amino acids were not affected by supplementation. Plasma urea and haptoglobin were not different between Lys treatments and control (P > 0.15). In the finishing phase, steers previously fed Lys-6 had daily gains 0.05 kg/day numerically greater than control and Lys-3 (P = 0.17). Carcass weights were 7.1 and 3.4 kg heavier than control for Lys-6 and Lys-3, respectively. Bloodmeal did not affect performance during the growing or finishing period. This study indicated ruminally protected Lys supplementation during the growing phase tended to improve performance of cattle during growing and finishing phases and resulting carcass weight. The second study was conducted using 45 (5- to 9-day old) milk-fed Holstein-Angus steer calves (40.9 ± 3.6 kg) supplemented 0, 1, or 2 g guanidinoacetic acid (GAA) per day (Creamino; Alzchem Trostberg GmbH, Trostberg, Germany) in the milk replacer for 42 days. Calves were grouped into blocks of 3 by arrival body weight and total serum protein, and each calf within a block was assigned a different treatment. Daily treatments were divided into 2 daily feedings where calves received 2.84 L of milk replacer (25% protein, 24% fat) at each feeding. Treatment ceased after 42 days and the 17-day weaning period was initiated. From day 42 to 48 calves were fed 1.89 L of milk replacer twice daily, 1.89 L of milk replacer was fed once daily from day 49 to 55, and no milk replacer was provided after day 55. Starter feed and water were provided for ad libitum intake for the entirety of the trial. Intake of milk replacer and starter feed were recorded. Health was assessed and scored twice daily for respiratory disease, fecal consistency, and lameness during treatment provision and once daily during the weaning phase. Body weight and hip height were measured on day 0, 14, 28, and 42. Body weight was also measured on day 59 (weaning weight). Due to death loss and removal of 1 calf, performance data of 41 calves were analyzed as a randomized block design. There was a tendency for body weight to linearly increase with increasing GAA by day 59 (linear, P = 0.09). Hip height increased with increasing GAA on day 14 (linear, P = 0.005). With GAA supplementation, there were tendencies for increases in average daily gain from day 0 to 42 (linear, P = 0.15) and day 42 to 59 (linear, P = 0.14). Overall, average daily gain tended to increase with increasing GAA (linear, P = 0.09). During all time periods, starter feed intake tended to linearly increase (P ≤ 0.07) with GAA supplementation. The 2 levels of GAA supplementation yielded similar results during the trial. No significant differences among treatments (P > 0.05) were observed in health scores during treatment or weaning phases. This study suggests inclusion of GAA in milk replacer tended to increase gain of calves, and this was associated with elevated starter intake.
Keywords: Cattle; Corn; Lysine; Guanidinoacetic acid; Milk-fed